Information on advances and trends in food sciences - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The quarterly Journal of Food Technology in Africa includes original papers and reviews on all aspects of food science, technology, and nutrition.Subscription (four issues). Institutions: $77.00 , Euro 74.00. Individuals: $73.00, Euro 70.00....